Strategi Harian Serambi Indonesia Dalam Meningkatkan Pemberitaan Bagi Publik - Muzakkir Muzakkir; Rahmalia Rahmalia (Publikasi Indonesia, 2022)
This research is motivated by the intense competition of the mass media so that it requires mass media companies to package their information with good quality. This study aims to examine and find out how the strategy carried out by Serambi Indonesia Daily in improving the quality of reporting for the public. This study uses qualitative research methods with three informants. Data collection techniques were carried out through observation, interviews, documentation, and the internet. The results of the author's research found that the strategies applied by the Serambi Indonesia Daily to improve the quality of reporting were increasing human resources (HR), increasing work facilities, increasing issue content and evaluating. The factors that influence Serambi Indonesia in improving the quality of news coverage are circulation (number of prints sold) and advertisements. Several strategies and factors carried out by Serambi Indonesia Daily are considered capable of improving the quality of its reporting. This can be seen from the number of print media and online media circulation, as well as the number of customers who advertise on Serambi Indonesia, both from government and private agencies.